Islamic Learning Management In Fostering The Value Of Spirituality In Integrated Islamic Elementary School Bina Anak Muslim Singkawang - Zikriadi; Syahruddin Usman; Abdul Rahman Sakka; Arnadi (IJGIE (International Journal of Graduate of Islamic Education), 2025)
The purpose of this study is to analyze how the management of the development of the Islamic Religious Education system at SDIT Bina Anak Muslim Singkawang in fostering students' spiritual values. Most existing studies focus more on the effectiveness of Islamic learning methods without linking them in depth with the educational management strategies applied. This research uses a descriptive qualitative approach with a field study method. Data were collected through observation, in-depth interviews, interviews, and other supporting documents related to how the management of Islamic Education system development at SDIT Bina Anak Muslim Singkawang in fostering students' spiritual values. In this study, the primary data sources are the Principal, Islamic Religious Education Teacher, Parents of students. Written data sources can be divided into sources from books and scientific magazines, data sources and archives, documents. The results showed that development management in Islamic learning qualifications at SD. SDIT BIAM Singkawang to foster students' spiritual values is done with various learning strategies. There are several strategies applied by teachers to improve students' spiritual values at SDIT BIAM Singkawang, including getting students used to saying greetings to others and practicing by shaking hands, applying a disciplined attitude towards students, fostering a love of knowledge towards students, getting students to obey the rules that apply at school, getting students used to being friendly to others, getting students to always live healthy, applying good manners to students, fostering a caring attitude towards the environment, building a sense of responsibility towards students and fostering self-confidence in students.